2022
DOI: 10.5114/biolsport.2021.102919
|View full text |Cite
|
Sign up to set email alerts
|

Training load responses to football game profile-based training (GPBT) formats: effects of locomotive demands manipulation

Abstract: The aim of this study was to compare internal and external load profiles of different game profile-based training (GPBT) formats among elite young football players. Twenty-one participants (age: 18.7 ± 0.6 years) performed three sessions of three GPBT formats, which were matched for training volume but structured with different high-speed running and sprint demands: i) performed along linear paths (GPBT-L); ii) performed as repetitive actions of short distance including many multi-directional changes of direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Therefore, we suggest practitioners avoid focusing only on the use of RPE but to integrate external and internal load parameters in their monitoring system. These suggestions are supported by previous research that found very similar RPE scores during soccer-specific training protocols ( 30 ), although the accelerations and HSR demands of these formats were significantly different among them. The data reported in the literature ( 8 , 12 , 30 ), in addition to what found in the current research suggest the necessity for practitioners of assessing external load parameters in soccer to have a more complete understanding of players' training load.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, we suggest practitioners avoid focusing only on the use of RPE but to integrate external and internal load parameters in their monitoring system. These suggestions are supported by previous research that found very similar RPE scores during soccer-specific training protocols ( 30 ), although the accelerations and HSR demands of these formats were significantly different among them. The data reported in the literature ( 8 , 12 , 30 ), in addition to what found in the current research suggest the necessity for practitioners of assessing external load parameters in soccer to have a more complete understanding of players' training load.…”
Section: Resultssupporting
confidence: 85%
“…This is a critical point because sided-games are extremely popular training formats in soccer ( 7 ) but generally fail to fully prepare players for the high-speed demands of the game ( 8 ). Practitioners should therefore add other drills to their training routine ( i.e., ball-based circuit drills) ( 30 ) and linear sprinting exercises (without the ball) to prepare their players for competition ( 19 , 33 ). Sided-games are also used to generate a mechanical load in soccer players, mainly because they offer exposure to acceleration and deceleration actions ( 15 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach can offer useful insights to coaches and practitioners, who should replicate the analysis reported in this study and use the resulting data to design the most suitable training sessions and adopt the most ecological drills to obtain the long-term physical adaptations needed to progress from an academy squad (i.e., U18) to an U23 or 1ST team (Beato et al, 2019a;Dello Iacono et al, 2019). In this study, we have found that high-intensity metrics such as HSR (significant group differences reported in the ANOVA but not following the post hoc analysis) and sprinting can discriminate between age groups as well as high-intensity bursts distance; therefore, sport scientists may include these metrics when monitoring and planning sport-specific drills, which can be beneficial to enhance the performance capacities required during a match (Dello Iacono et al, 2022). The importance and the rationale for the monitoring and implementation of HSR and sprinting have been recently discussed in detail (for further indepth consideration, please see Beato et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…More recently, a game profile-based training (GPBT) approach has been proposed to induce relative HSR and sprint running distances comparable or greater than matches outcomes in under 19 elite male soccer players ( 87 ). A GPBT could be defined as 1 or more bouts of physical and technical activities (e.g., high-intensity intermittent running, changes of direction, and passes), which replicate the type of movements and physical demands (e.g., internal and external loads) of match-play ( 88 ). It was reported that a GPBT was more demanding in terms of distance run above 19 and 25.2 km·h −1 compared with a 5v5 small sided-game in a 42 × 30 m pitch (i.e., 126 m 2 per player), specifically, 10.2 m·min −1 during GPBT vs. 4.6 m·min −1 during small sided-game for HSR and 4.2 vs. 2.0 m·min −1 for sprinting ( 87 ).…”
Section: Discussionmentioning
confidence: 99%